1986
DOI: 10.1002/jso.2930310410
|View full text |Cite
|
Sign up to set email alerts
|

Histiocytoid carcinoma: A variant of breast cancer

Abstract: The history of a patient presenting with metachronous bilateral breast cancer displaying histiocytoid features is reviewed. Although regional metastases were noted, this patient has not demonstrated an aggressive systemic disease pattern. In the past, histiocytoid breast cancer has been classified as either a lipid-rich carcinoma or as a variant of lobular carcinoma. However, histiocytoid carcinoma should be considered a distinct entity. Unlike the lipid-rich carcinomas, this tumor stained strongly for mucin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The prognosis of histiocytoid carcinoma is still controversial, several prior reports indicated that histiocytoid carcinoma has a relatively unfavorable prognosis, that is, lymph node metastases [3,14,21,39] and remote metastases [2,11,14,24,38,40]. Moreover, the clinical course of HLC remains unclear due to no sequential studies of HLC [3,20,21,27], except Eusebi et al [16] who explained that a number of HLC cases were not particularly aggressive behavior.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The prognosis of histiocytoid carcinoma is still controversial, several prior reports indicated that histiocytoid carcinoma has a relatively unfavorable prognosis, that is, lymph node metastases [3,14,21,39] and remote metastases [2,11,14,24,38,40]. Moreover, the clinical course of HLC remains unclear due to no sequential studies of HLC [3,20,21,27], except Eusebi et al [16] who explained that a number of HLC cases were not particularly aggressive behavior.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, histiocytoid cytological features were emphasized by the diffuse infiltration of inflammatory cells and/or fibrous stroma in several previous cases [21,24,26,38] and in our cases. Since Hood et al [24] first described this tumor in 1973 and used the term 'histiocytoid carcinoma' for a tumor mainly composed of histiocyte-like cells, histiocytoid carcinomas have been reported for a mixture of ductal and lobular carcinomas [16,21,24,39]; however, several authors consider a number of cases of histiocytoid carcinoma as being of lobular origin because of the lack of E-cadherin expression, in addition to infiltrating in single file or a targetoid pattern and the coexistence of in situ lobular carcinoma component [2,11,14,18,26,38,40].…”
Section: Discussionmentioning
confidence: 99%
“…It has since been variously ascribed to lobular or apocrine carcinoma,2–9 as well as being linked to lipid-rich carcinoma,1 10 with some authors advocating that it be considered a distinct entity 11…”
mentioning
confidence: 99%
“…3,6,15,18,[20][21][22][23] It was difficult for us to distinguish PLC with apocrine differentiation from apocrine carcinoma in cytologic preparations. Both tumors represent abundant and granular cytoplasm, distinct cell border and conspicuous nucleoli, which indicate apocrine differentiation.…”
Section: Discussionmentioning
confidence: 99%